170 Comparing the performance of two interferon-gamma release assays in autoimmune skin disease patients: a prospective study. (April 2019) - Krain, Rebecca L; Gaffney, Rebecca G; Keyes, Emily R; Feng, Rui; Werth, Victoria P
Abstract : Background: Autoimmune skin disease patients are standardly screened for tuberculosis via interferon-gamma release assays (IGRAs) prior to starting new immunosuppressive drugs or enrolling in clinical trials. Two commercial IGRAs, T-SPOT.TB and QuantiFERON-Tb Gold (QFT-G), are reported as either determinate (positive or negative) or indeterminate. Both tests utilize similar immunoenzymatic reactions for interferon-gamma detection, but differ in its quantification. Though the QFT-G is more widely used, studies have demonstrated that the T-SPOT.TB has lower rates of indeterminate results in immunosuppressed patients, and thus may prevent a delay in the initiation of necessary therapies or enrollment in clinical trials. The newest generation of QFT-G, the QuantiFERON-TB Gold Plus (QFT-Plus), has not been compared to the T-SPOT.TB in this patient population. We aim to investigate the performance of both the T-SPOT.TB and QFT-Plus, as indeterminate results represent a major barrier to receiving appropriate treatment in autoimmune skin disease patients. Methods: This ongoing prospective study included 48 patients seen at the Hospital of the University of Pennsylvania. Venous blood samples were collected from patients and underwent tuberculosis screening with QFT-Plus and T-SPOT.TB IGRAs. The proportions of indeterminate and determinate (positive and/or negative) results among the two tests were compared. Results: In the study population of 48 patients, 29% had a primary diagnosis of cutaneous lupus (n=14). There were 2 indeterminate results with the QFT-Plus and no indeterminate results with T-SPOT.TB. There was also one positive result that was seen with both the QFT-Plus and T-SPOT.TB. All patients with a primary diagnosis of cutaneous lupus had negative results for both QFT-Plus and T-SPOT.TB. Using a one-tailed Fischer test, there was no statistical significance when comparing QFT-Plus and T-SPOT.TB in autoimmune skin disease patients (p=0.25). Conclusions: In this prospective study, the T-SPOT.TB had fewer indeterminate results compared to the QFT-Plus. Though this finding was not statistically significant, it is clinically important as indeterminate results preclude autoimmune skin disease patients from receiving necessary treatment. Compared to previous studies on the older generation of the QFT-G test, the QFT-Plus showed improvement in reducing the amount of indeterminate results. Despite this, we suggest using the T-SPOT.TB in tuberculosis screening for autoimmune skin disease patients who have an indeterminant QFT-G or QFT-Plus, as this test did not display any indeterminate results. The results of this study are limited by the small sample size. Funding Source(s): This project was supported by Oxford Immunotec, Inc.